2016
DOI: 10.1021/jacs.6b04175
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Selective Photocatalytic Hydrogenation of Cinnamaldehyde over Au/SiC Catalysts

Abstract: Highly selective hydrogenation of cinnamaldehyde to cinnamyl alcohol with 2-propanol was achieved using SiC-supported Au nanoparticles as photocatalyst. The hydrogenation reached a turnover frequency as high as 487 h(-1) with 100% selectivity for the production of alcohol under visible light irradiation at 20 °C. This high performance is attributed to a synergistic effect of localized surface plasmon resonance of Au NPs and charge transfer across the SiC/Au interface. The charged metal surface facilitates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
171
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(181 citation statements)
references
References 39 publications
5
171
0
1
Order By: Relevance
“…Furthermore, control experiments performed with styrene and anisole as the substrates indicated that no reaction occurred, which verified the inertness of Hf‐Phy for the transfer hydrogenation of ORMs, and this led to high selectivities for the corresponding alcohols with unreduced ORMs. Finally, some aliphatic α,β‐unsaturated aldehydes could also be converted over Hf‐Phy (Table , entries 16 and 17), but the conversions and selectivities to the corresponding alcohols were not satisfactory owing to the difference in the conjugation effects of the unsaturated double bonds …”
Section: Figurementioning
confidence: 99%
“…Furthermore, control experiments performed with styrene and anisole as the substrates indicated that no reaction occurred, which verified the inertness of Hf‐Phy for the transfer hydrogenation of ORMs, and this led to high selectivities for the corresponding alcohols with unreduced ORMs. Finally, some aliphatic α,β‐unsaturated aldehydes could also be converted over Hf‐Phy (Table , entries 16 and 17), but the conversions and selectivities to the corresponding alcohols were not satisfactory owing to the difference in the conjugation effects of the unsaturated double bonds …”
Section: Figurementioning
confidence: 99%
“…Unsaturated alcohols are valuable chemical intermediates and widely used in pharmaceuticals, perfumes, and flavors [1,2]. Selective hydrogenation of α,β-unsaturated aldehydes to the corresponding unsaturated alcohols is a scientific challenge in heterogeneous catalysis because hydrogenation of the conjugated C=C bond is thermodynamic and kinetically favored, in comparison to that of the C=O group [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This finding contradicts the prediction of the classical massdifference model of impurity scattering, according to which the effects of BC and NC would be similar and much smaller than that of the C vacancy. The strikingly different behavior of the BC defect arises from a unique pattern of resonant phonon scattering caused by the broken structural symmetry around the B impurity.Silicon carbide (SiC) plays a fundamental role in many emerging technologies, ranging from biomedical sensors to optoelectronics, power electronics and photovoltaics [1][2][3][4][5][6][7][8][9]. Most notably, this material has been termed the "linchpin to green energy" that may replace Si-based technology in power electronics [1], owing partly to its large lattice thermal conductivity (κ).…”
mentioning
confidence: 99%